The study of protection of operators and surrounding workers at the time of using portable intraoral X-ray unit. (July 2018) - Iwawaki, Atsushi; Otaka, Yusei; Asami, Ruri; Ozawa, Tomonori; Izawa, Maki; Saka, Hideki
Highlights: Aiming at management of operator and surrounding worker exposure. It was suggested that using shield was effective for the exposure reduction. Surround workers should avoid working in anterior and make an effort for protection.